1993
DOI: 10.1002/qua.560460111
|View full text |Cite
|
Sign up to set email alerts
|

On the solid state of hydrogen fluoride: A self‐consistent crystal field study

Abstract: A recently developed self-consistent crystal field (SCCF) method is applied to two suggested crystal structures of solid hydrogen fluoride, polar and nonpolar, respectively. Constrained geometry optimizations are performed and the results are compared with experiment and previous theoretical studies. Comparisons are also made with a previous SCCF study on hydrogen cyanide. The Pauli repulsion, dispersion, and "classical" crystal field contributions to the lattice energy are calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
3
6
0
Order By: Relevance
“…71 There have been several previous theoretical studies of the relative energies of the nonpolar and polar forms. 72,73 Most recently Sode et al 72 concluded that the nonpolar structure is more stable.…”
Section: Hydrogen Fluoridementioning
confidence: 99%
“…71 There have been several previous theoretical studies of the relative energies of the nonpolar and polar forms. 72,73 Most recently Sode et al 72 concluded that the nonpolar structure is more stable.…”
Section: Hydrogen Fluoridementioning
confidence: 99%
“…38,39,40,41,42,43,44,45 This facilitates the determination of the correlation contribution to the binding energy of infinite chains from the energy increments in oligomers using Eq. (5). Yet the virtual Wannier orbitals involved in the determination of the energy increments, and implicitly contained in Eq.…”
Section: Theorymentioning
confidence: 99%
“…Hydrogen fluoride 1,2,3,4,5,6 and hydrogen chloride 7,8,9 are representatives of molecular crystals; the electronic structure of the constituent HF or HCl monomers is essentially preserved upon crystallization. The monomers in both crystals are hydrogen bonded; 10,11,12,13,14 it is a directional and anisotropic bonding of the hydrogen in a HF and HCl monomer to the fluorine or chlorine atom, respectively, of a neighboring monomer.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen fluoride 1,2,3,4,5 and hydrogen chloride 6,7 are representatives of hydrogen-bonded crystals. This type of bonding 8,9,10,11,12 is weak and essentially preserves the electronic structure of the constituent HF and HCl monomers, respectively.…”
Section: Introductionmentioning
confidence: 99%